Constraints Obstructing the Smooth Operation of the Capital Markets of Bangladesh and Probable Solutions to These Constraints: An Empirical Study Based on Investors’ Perception - Ghosh, Protap Kumar; Bose, Tarun Kanti; Shahriar, Masum (Indian Journal of Finance, 2012)
This study was directed towards finding out the problem areas which are causing problems in the capital markets of Bangladesh. The investigation of such problems has been done after collecting the opinions of the investors through structured interviews with a well-documented questionnaire. Retail investors reckon incorrect price manipulation, insider trading, weak framework and policies as the main problems obstructing the development of the capital markets. They also notified that improper dividend policy, wrong valuation or corruption in SEC/DSE have a significant impact on the fluctuations of the markets. This study also covered the responses of the investors regarding the probable solutions suggested by the experts of the security markets. The investors feel that to get a better environment in this market, the concerned authorities should exercise the demutualization process as soon as possible and stop the insider trading. Strong and effective legal framework, standard face value and market lot, balance between demand and supply, surveillance of the central bank, and a strong and effective legal framework are pertinent to solve the problems that plague the capital markets of Bangladesh.